OPTIMALISASI TATA RUANG DAN ETALASE UNTUK MENINGKATKAN DAYA TARIK KONSUMEN - Erita Riski Putri; Rezzi Nanda Bariski; Nur Desilawati (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to optimize spatial arrangement and display layout to enhance consumer appeal for the Micro, Small, and Medium Enterprises (MSMEs) of the Komunitas Sukses Berjamaah Indonesia (KSBI) in South Jakarta. Lecturers from IBI Kosgoro 1957 participated in this activity, focusing on improving the effectiveness of spatial arrangement and displays, which will positively impact sales and the growth of the MSMEs. This activity began with an outreach to KSBI members on the importance of an attractive spatial arrangement and display to capture consumer attention. In this outreach, the IBI Kosgoro 1957 lecturers shared knowledge and practical experience on effective spatial design and marketing strategies through appealing displays. After the outreach, an analysis of the spatial arrangement and displays at KSBI was conducted to identify areas that needed improvement. The lecturers and their team collaborated with KSBI members to redesign the layout and displays, making them more attractive and functional. They considered factors such as product arrangement, lighting, visual merchandising, and efficient space management. Next, the implementation of changes to the layout and displays was carried out in collaboration between the IBI Kosgoro 1957 lecturers, their team, and KSBI members. They worked together to plan and execute the necessary changes. The IBI Kosgoro 1957 lecturers provided guidance and recommendations to KSBI members in optimizing their spatial arrangement and displays. The results of this activity are expected to enhance consumer appeal towards KSBI MSMEs. With effective spatial arrangements and attractive displays, MSME products are expected to be better showcased and catch the attention of consumers, ultimately boosting sales and business growth for KSBI members. This community service activity also provided KSBI members with knowledge and skills in managing their spatial arrangements and displays. They can apply design principles to increase the effectiveness of their spatial arrangements and displays in the future.